Wetting and interfacial behavior of Fe-based self-fluxing alloy-refractory compound systems - Umanskyi, O.P.; Umanskyi, O.P.; Storozhenko, M.S.; Krasovskyy, V.P. (Сверхтвердые материалы, 2017)
In this study the wettability and interfacial behaviour of the TiC–FeNiCrBSiC and TiB₂–FeNiCrBSiC systems were investigated. The wetting experiments were performed by the sessile drop method at 1150 °C under a vacuum. The contact angles of TiC and TiB₂ wetting by melted Fe-based self-fluxing alloy were 51° and 36°, respectively. Thermodynamic calculations were carried out to understand the metal-ceramic interaction mechanism in the TiC–FeNiCrBSiC and TiB₂–FeNiCrBSiC systems. The structure of the interface region in the TiB₂–FeNiCrBSiC system was characterized by the optical microscopy and SEM-EDS analysis. The formation of Fe, Ni, Cr and Mo complex borides was revealed within the interface region of the TiB₂–FeNiCrBSiC system. Досліджено змочування та контактну взаємодію в системах TiC–FeNiCrBSiC і TiB₂–FeNiCrBSiC. Кінетику змочування вивчено методом “лежачої краплі” в вакуумі при температурі 1150 °C. Кути змочування TiC і TiB₂ самофлюсівним сплавом на основі заліза становили 51° і 36° відповідно. Для виявлення особливостей контактної взаємодії на межі металевий сплав–кераміка проведено термодинамічні розрахунки систем TiC–FeNiCrBSiC і TiB₂–FeNiCrBSiC. Методами оптичної та скануючої електронної мікроскопії вивчено структуру зони взаємодії в системі TiB₂–FeNiCrBSiC. Виявлено формування складних боридів Fe, Ni, Cr і Mo в зоні взаємодії системи TiB₂–FeNiCrBSiC. Исследовали смачивание и контактное взаимодействие в системах TiC–FeNiCrBSiC и TiB₂–FeNiCrBSiC. Кинетику смачивания изучали методом “лежащей капли” в вакууме при температуре 1150 °C. Углы смачивания TiC и TiB₂ самофлюсующимся сплавом на основе никеля составляли 51° и 36° соответственно. Для выявления особенностей контактного взаимодействия на границе металлический сплав–керамика были проведены термодинамические расчеты систем TiC–FeNiCrBSiC и TiB₂–FeNiCrBSiC. Методами оптической и электронной микроскопии изучали структуру зоны взаимодействия в системе TiB₂–FeNiCrBSiC. Установлено формирование сложных боридов Fe, Ni, Cr и Mo в зоне взаимодействия системы TiB₂–FeNiCrBSiC.